2008
DOI: 10.1103/physrevlett.100.127202
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Large Magnetoresistance in Boron-Doped Silicon

Abstract: Boron-doped Si-SiO2-Al structures are fabricated to study extremely large magnetoresistance (MR) effects. Current-voltage characteristics show a nonlinear behavior, dominated by an autocatalytic process of impact ionization. At low temperatures, the magnetic field postpones the onset of impact ionization to higher electric fields. This results in a symmetric positive MR of over 10,000% at 400 kA/m. Applying a magnetic field leads to an increase of the acceptor level compared to the valence band as deduced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 18 publications
8
85
1
Order By: Relevance
“…In In stark contrast to many MR phenomena observed in several other material systems in which the strength of the MR tends to quench with increasing temperature [14,[23][24][25], in our short InAs channels the large MR is observed over an extended temperature range. This is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 52%
“…In In stark contrast to many MR phenomena observed in several other material systems in which the strength of the MR tends to quench with increasing temperature [14,[23][24][25], in our short InAs channels the large MR is observed over an extended temperature range. This is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Schoonus et al 16 attributed the observed shift to the high-energy region to the fact that the magnetic field shrinks the acceptor wave functions and, thus, leads to a decrease in the overlap of the tales of the functions of neighboring acceptor centers. As a result, the effective energy of acceptor level increases.…”
Section: A Magnetoimpedance: Low Biasmentioning
confidence: 99%
“…It was only recently, however, that a large magnetoresistance (MR) has been reported [1][2][3][4] . MR is the change in resistivity ρ of a material in a magnetic field B relative to the zero field resistivity: ∆ρ/ρ = [ρ(B) − ρ(0)]/ρ(0).…”
Section: Introductionmentioning
confidence: 99%